2016
DOI: 10.1007/s10735-016-9707-y
|View full text |Cite
|
Sign up to set email alerts
|

Histological evidence that metformin reverses the adverse effects of diabetes on orthodontic tooth movement in rats

Abstract: This study evaluated the effects of metformin on orthodontic tooth movement in a rat model of type 2 diabetes mellitus. Rats were fed a high-fat diet for 4 weeks to induce fat accumulation and insulin resistance, and then injected with a low dose of streptozotocin (35 mg/kg) intraperitoneally to induce type 2 diabetes. An orthodontic appliance was placed in normoglycemic, type 2 diabetes, and type 2 diabetes with metformin-administrated rats. After 14 days, type 2 diabetes rats exhibited greater orthodontic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 46 publications
0
33
0
1
Order By: Relevance
“…Studies utilizing various in vivo models of insulin resistance and/or hyperglycemia also generally confirm that metformin monotherapy is bone‐friendly, with ability to counteract the detrimental effects of diabetes on bone. Specifically, metformin has been shown to prevent or correct the diabetes‐induced alterations in bone microarchitecture and/or bone histology in models of partial insulin deficiency and in models of insulin resistance, diet‐induced obesity, or metabolic syndrome . At the same time, bone marrow adipose expansion, characteristic of mice fed a high‐fat diet, was also correctible with metformin .…”
Section: Drugs and Bonementioning
confidence: 99%
“…Studies utilizing various in vivo models of insulin resistance and/or hyperglycemia also generally confirm that metformin monotherapy is bone‐friendly, with ability to counteract the detrimental effects of diabetes on bone. Specifically, metformin has been shown to prevent or correct the diabetes‐induced alterations in bone microarchitecture and/or bone histology in models of partial insulin deficiency and in models of insulin resistance, diet‐induced obesity, or metabolic syndrome . At the same time, bone marrow adipose expansion, characteristic of mice fed a high‐fat diet, was also correctible with metformin .…”
Section: Drugs and Bonementioning
confidence: 99%
“…Orthodontic tooth movement (OTM) occurs through controlled application of mechanical forces to the tooth, which leads to required changes in the periodontal ligament and alveolar bone and subsequently activates remodeling of the alveolar bone (Verna et al 1999 ; Nakamura et al 2008 ; Tsuge et al 2016 ; Sun et al 2017 ). The periodontal ligament, a connective mechanosensitive fibrous soft tissue located between the root and the alveolar bone, mediates the loading force from tooth to alveolar bone, and thus creates the necessary conditions for cells to participate in alveolar bone remodeling (Liu et al 2013 ; Mabuchi et al 2002 ; Cui et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of numerous clinical observations and experimental studies, pathological changes in bone tissue, significant microcirculatory disorders, and neurotrophic disorders were identified among the preexis ting adverse factors affecting the course of the postoperative period of patients with DM. At the same time, it is believed that osteopenia and osteoporosis, as the most frequent pathological changes in bone tissue, have the diffuse character, since both cancellous and tubular bones "suffer" [14]. Conducted histomorphometric studies have shown that in case of diabetes mellitus type 1 there is a reduced bone formation with a decrease in metabolic processes in it.…”
Section: Discussionmentioning
confidence: 99%